Improving the effectiveness of the interaction of the investigator with pre-trial organs in the Republic of Uzbekistan - Karimova, Dilrabo (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article deals with the questions concerning improvement of improving the effectiveness of the criminal procedural interaction of the investigator with pre-trial organs, international aspects of cooperation of states in crime control, peculiarities of procedural interrelations between the investigator and subdivisions criminal search in detection and investigation of crimes. Legal aspects of improvement of national legislation and international cooperation in crime control are considered